2015
DOI: 10.1016/j.bbrc.2015.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Co-purification of arrestin like proteins with alpha-enolase from bovine myocardial tissues and the possible role in heart diseases as an autoantigen

Abstract: We suggest a possible interaction between ALP and alpha-enolases yielding a complex that may be involved in the induction of cardiac autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Translocation of ENO1 to the cell surface can drive the production of specific ENO1 autoantibodies, causing autoimmune diseases. In the infarcted heart, β-arrestin associates with ENO1 and translocates together to the cell membrane as auto-antigens, thus inducing high levels of anti-ENO1 and anti-arrestin antibodies in patients' sera [27]. We confirmed the co-expression of ENO1 and β-arrestin in EVT in the first trimester placenta of uRM patients (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Translocation of ENO1 to the cell surface can drive the production of specific ENO1 autoantibodies, causing autoimmune diseases. In the infarcted heart, β-arrestin associates with ENO1 and translocates together to the cell membrane as auto-antigens, thus inducing high levels of anti-ENO1 and anti-arrestin antibodies in patients' sera [27]. We confirmed the co-expression of ENO1 and β-arrestin in EVT in the first trimester placenta of uRM patients (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…9). β-arrestin plays a role in G-protein receptor desensitization, receptor endocytosis, activation of extracellular signal regulated kinases and other mitogen activated protein kinases [27]. ENO1 can also be translocated to the cell surface by extracellular peptidyl arginine deiminase [20] and lipopolysaccharides [28].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may explain an occasional detection of anti-enolase and anti-arrestin AAbs in the same patient with CAR or MS, suggesting that such complexes could be released from damaged photoreceptor cells, then processed by antigen-presenting cells (38, 47). Surprisingly, AAbs against arrestin and α-enolase were also reported in some patients with coronary heart disease (48). When investigators exposed cardiomyocytes to monoclonal antibody against arrestin or enolase in vitro , they observed decreased cell proliferation, suggesting that antibodies bound to the membrane-exposed epitopes of arrestin and enolase in living cells (48).…”
Section: Enolasementioning
confidence: 99%
“…Surprisingly, AAbs against arrestin and α-enolase were also reported in some patients with coronary heart disease (48). When investigators exposed cardiomyocytes to monoclonal antibody against arrestin or enolase in vitro , they observed decreased cell proliferation, suggesting that antibodies bound to the membrane-exposed epitopes of arrestin and enolase in living cells (48). The study suggested that these AAbs may be involved in the induction of cardiac autoimmune diseases.…”
Section: Enolasementioning
confidence: 99%